A new insight into the impact of copy number variations on cell cycle deregulation of luminal-type breast cancer - Amir Mahdi Khamaneh; Davoud Jafari-Gharabaghlou; Khalil Ansarin; Khalil Ansarin; Khalil Ansarin; Pouya Pazooki; Zahra Akbarpour; Behrooz Naghili; Behrooz Naghili; Nosratollah Zarghami; Nosratollah Zarghami (Oncology Reviews)
Breast cancer is the most prevalent neoplasm in women. ER+ (Luminal subtype), representing over 70% of breast tumors, is a genetically diverse group. Structural and Numerical-Chromosomal instability initiates tumor development and is recognized as the primary driver of genetic alteration in luminal breast tumors. Genomic instability refers to the increased tendency of cancer cells to accumulate genomic alterations during cell proliferation. The cell cycle check-point response to constant and stable genomic alterations in tumor cells drives this process. The impact of CNV patterns and aneuploidies in cell cycle and proliferation perturbation has recently been highlighted by scientists in Luminal breast tumors. The impact of chromosomal instability on cancer therapy and prognosis is not a new concept. Still, the degree of emerging genomic instability leads to prognosis alteration following cell cycle deregulation by chromosomal instability could be predicted by CNVs-based reclassification of breast tumors. In this review, we try to explain the effect of CIN in the cell cycle that ended with genomic instability and altered prognosis and the impact of CIN in decision-making for a therapy strategy for patients with luminal breast cancer.